2015
DOI: 10.1387/ijdb.150211jp
|View full text |Cite
|
Sign up to set email alerts
|

Calcium signals regulated by NAADP and two-pore channels - their role in development, differentiation and cancer

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 148 publications
1
7
0
Order By: Relevance
“…These new data support our previous findings that localized TPC2-mediated Ca 2+ release might act upstream of more widespread Ca 2+ release from IP 3 Rs (predominantly during SP1) and RyRs (predominantly during SP2). Our new data also support the trigger hypothesis of NAADP-mediated Ca 2+ signaling, and the role of TPC2 as an upstream regulator of the ER/SR-residing IP 3 Rs and RyRs (Cancela et al, 1999; Kinnear et al, 2004, 2008; Patel et al, 2010; Galione, 2011; Kelu et al, 2015; Parrington et al, 2015). The contrasting roles of the ER/SR-Ca 2+ channels during myogenesis have previously been demonstrated in C2C12 myoblasts, where IP 3 R-mediated signaling has been shown to play a role in differentiation (Porter et al, 2002), whereas RyR-mediated signaling is not necessary for the early events (even though RyR are expressed in C2C12 cells at this stage), but it is involved in EC-coupling in the mature skeletal muscle (Aley et al, 2010).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…These new data support our previous findings that localized TPC2-mediated Ca 2+ release might act upstream of more widespread Ca 2+ release from IP 3 Rs (predominantly during SP1) and RyRs (predominantly during SP2). Our new data also support the trigger hypothesis of NAADP-mediated Ca 2+ signaling, and the role of TPC2 as an upstream regulator of the ER/SR-residing IP 3 Rs and RyRs (Cancela et al, 1999; Kinnear et al, 2004, 2008; Patel et al, 2010; Galione, 2011; Kelu et al, 2015; Parrington et al, 2015). The contrasting roles of the ER/SR-Ca 2+ channels during myogenesis have previously been demonstrated in C2C12 myoblasts, where IP 3 R-mediated signaling has been shown to play a role in differentiation (Porter et al, 2002), whereas RyR-mediated signaling is not necessary for the early events (even though RyR are expressed in C2C12 cells at this stage), but it is involved in EC-coupling in the mature skeletal muscle (Aley et al, 2010).…”
Section: Discussionsupporting
confidence: 83%
“…There is a growing interest in the role played by two-pore channels (TPCs) and their link with nicotinic acid adenine dinucleotide diphosphate (NAADP) signaling with regards to their combinatorial contribution to the Ca 2+ -mediated regulation of differentiation and development (Calcraft et al, 2009; Patel et al, 2010; Galione, 2011; Morgan and Galione, 2014; Parrington and Tunn, 2014; Parrington et al, 2015; Brailoiu and Brailoiu, 2016). The various roles played by the Ca 2+ mobilizing messengers inositol 1,4,5-trisphosphate (IP 3 ) and cyclic adenosine diphosphate ribose (cADPR), and their respective receptors in the endoplasmic/sarcoplasmic reticulum (ER/SR) membrane, are well established (Berridge, 1993; Lee, 1993; Berridge et al, 2003; Mikoshiba, 2007; Lanner et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study showed that most iron in cortical neurons is located in microsomal fractions containing the endoplasmic reticulum and vesicles (Reinert et al, 2019), suggesting that the endolysosomal system is a major iron storage site in cortical neurons, and efflux of iron from these stores can impact neuronal homeostasis. Morphine may promote iron efflux through several endolysosomal conduits, including DMT-1 (Gunshin et al, 1997), two-pore channels (Parrington et al, 2015), and TRPML1 (Dong et al, 2008; Bae et al, 2014). TRPML1 regulates endolysosomal function by releasing cations from endolysosomes, most notably calcium and iron (Dong et al, 2008; Shen et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Links between TPCs and cancer have been summarized in a recent review by Parrington et al (2015) [ 37 ]. In addition, Nguyen et al [ 13 ] have recently shown that TPCs play a crucial role in cancer cell migration and tumor cell dissemination, as silencing TPC1 and TPC2 with siRNA or pharmacological inhibition reduces the adhesion and migration of invasive tumor cells and the formation of lung metastases in an in vivo mouse model.…”
Section: Tpcs and Cancermentioning
confidence: 99%